1990
DOI: 10.2166/wst.1990.0091
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Textile Industry in Turkey – Pollution Profiles and Treatability Characteristics

Abstract: In this study, a large number of textile plants in Turkey have been studied and evaluated in terms of characteristics and treatability of wastewaters involved as related to relevant production parameters, exhibiting significant differences for each plant. Certain industrial groups have been identified to possess different pollution profiles and treatability specifications within the same subcategory. The results observed lead to conclude that the suhcategorization now in use for the textile industry needs to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
1
1
0
1
Order By: Relevance
“…The table indicates a close agreement between the findings of this study and the experimental data reported in the literature for another denim‐processing plant 8. The information displayed in the table supports the previously mentioned argument2 that subcategorization can hardly be justified on the basis of conventional parameters; only denim processing can be singled out from the rest, due to its excessive inorganic suspended solids content requiring an effective pretreatment before a biological treatment step. The rest is observed to exhibit a common feature of high organic and low nutrient contents with respect to domestic sewage.…”
Section: Results and Evaluationsupporting
confidence: 75%
See 1 more Smart Citation
“…The table indicates a close agreement between the findings of this study and the experimental data reported in the literature for another denim‐processing plant 8. The information displayed in the table supports the previously mentioned argument2 that subcategorization can hardly be justified on the basis of conventional parameters; only denim processing can be singled out from the rest, due to its excessive inorganic suspended solids content requiring an effective pretreatment before a biological treatment step. The rest is observed to exhibit a common feature of high organic and low nutrient contents with respect to domestic sewage.…”
Section: Results and Evaluationsupporting
confidence: 75%
“…This approach is only meaningful if it helps (a) to define a wastewater character specific and consistent for the subcategory; and (b) to identify a specific set of effluent limitations, justifiable with a particular treatment technology. A comprehensive review on this subject revealed that the proposed subcategories for textile were not meaningful on the basis of wastewater characterization using conventional parameters 2…”
Section: Introductionmentioning
confidence: 99%
“…Segundo GERMIRLI et al (1990), BANAT et al (1996) e TÜNAY et al (1996, as indústrias têxteis apresentam natureza complexa em termos da diversidade de materiais e produtos químicos aplicados em seus processos produtivos. Diferentes técnicas e uma gama bastante variável de operações e processos estão envolvidos dentro destas indústrias.…”
Section: Considerações Gerais Sobre O Processo Produtivo Têxtilunclassified